Integrating project-based learning and virtual kitchen: a digital learning innovation to enhance students’ creativity and entrepreneurial potential in bakery courses - Ifnalia Rahayu; Yuliana Yuliana; Wiwik Gusnita; Wiki Lofandri (JPGI (Jurnal Penelitian Guru Indonesia), 2025)
The demand for innovative approaches in vocational education has increased significantly in the digital era. This study explores the integration of Project-Based Learning (PjBL) with a Virtual Kitchen platform to enhance students’ creativity and entrepreneurial potential in bakery courses. Using a quasi-experimental pretest-posttest design with non-equivalent groups, the research involved 52 students divided into experimental (n = 26) and control (n = 26) groups. The intervention combined project-based tasks with virtual kitchen simulations, allowing students to experiment with recipes, simulate product branding, and practice digital marketing in a risk-free environment. Data were collected through creativity assessments, product evaluation rubrics, entrepreneurial attitude scales, and student feedback surveys. Statistical analysis using paired and independent t-tests revealed a significant improvement in both creativity and entrepreneurial readiness in the experimental group (p < 0.001). The findings highlight that integrating PjBL with Virtual Kitchen not only supports technical mastery but also nurtures digital micro-entrepreneurship and innovative thinking. This model presents a transformative strategy for preparing vocational students for the demands of Industry 4.0. Recommendations are provided for further implementation in other culinary domains and the development of more advanced virtual platforms.